Transtornos mentais comuns e qualidade de vida em cuidadores de usuários de um CAPS infanto-juvenil - Peixoto, Maristela Jaqueline Reis (2013)
This Master Dissertation has examined the prevalence of common mental disorders and the quality of life of caregivers of children and adolescents users of Children s CAPS (Psychosocial Care Center), in city in the center of Rio Grande do Sul. Specifically, it sought: raise sociodemographic characteristics; check the prevalence of common mental disorders; raise indices of quality of life; and check possible correlations between the variables. The work consists in a descriptive study, correlational and cross-sectional, quantitative approach. In this study 86 caregivers have participated, among them fathers, mothers, grandparents, uncles, brothers and husband. The study was submitted to and approved by the ethics committee of the Federal University of Santa Maria, where ethical procedures for research with human beings were respected. The tools used during the research were: a questionnaire of sociodemographic characteristics (this tool was adapted); SRQ-20 (Harding, 1980, Mari & Williams, 1986, Gonçalves et al., 2008) and WHOQOL-bref (Fleck et al., 2000). The data were tabulated and analyzed by means of a database created using the statistical package SPSS 17.0. Descriptive analysis (mean, frequencies, percentages, median, mode) and correlation analysis were performed. Pearson's Correlation Analysis was used, with evidence of statistical significance whenever p≤0,05. The results will be presented in two articles. The first article Prevalence of Common Mental Disorders (CMD) in caregivers of Children s CAPS - presents some results of sociodemographic characteristics and a prevalence of 74.7% of common mental disorders. Significant correlations were found between the variables. In Article 2 Evalution of quality of life in caregivers of users of Children s CAPS- are also presented some sociodemographic characteristics and results of quality of life that show that the caregivers present quality of life worthy of attention. Correlations between the variables are also presented. As a conclusion, it is realized that the caregivers need an adequate support in terms of treatment, and that actions are needed in this direction so that the same will be able to meet the responsibilities of care, aiming to health of all the involved.